Community based Primary Care for Adolescents and Young Adults Transitioning From Pediatric Specialty Care: Results from a Scoping Review. (March 2022) - Schraeder, Kyleigh; Allemang, Brooke; Felske, Ashley N.; Scott, Cathie M.; McBrien, Kerry A.; Dimitropoulos, Gina; Samuel, Susan
Background: Ongoing primary care during adolescence is recommended by best practice guidelines for adolescents and young adults (AYAs; ages 12-25) with chronic conditions. A synthesis of the evidence on the roles of Primary Care Physicians (PCPs) and benefits of primary care is needed to support existing guidelines. Methods: We used Arksey and O'Malley's scoping review framework, and searched databases (MEDLINE, EMBASE, PsychINFO, CINAHL) for studies that (i) were published in English between 2004 and 2019, (ii) focused on AYAs with a chronic condition(s) who had received specialist pediatric services, and (iii) included relevant findings about PCPs. An extraction tool was developed to organize data items across studies (eg, study design, participant demographics, outcomes). Results: Findings from 58 studies were synthesized; 29 (50%) studies focused exclusively on AYAs with chronic health conditions (eg, diabetes, cancer), while 19 (33%) focused exclusively on AYAs with mental health conditions. Roles of PCPs included managing medications, "non-complex" mental health conditions, referrals, and care coordination, etc. Frequency of PCP involvement varied by AYAs; however, female, non-Black, and older AYAs, and those with severe/complex conditions appeared more likely to visit a PCP. Positive outcomes were reported for shared-care models targeting various conditions (eg, cancer, concussion, mental health). Conclusion: Our findings drew attention to the importance of effective collaboration among multi-disciplinary specialists, PCPs, and AYAs for overcoming multiple barriers to optimal transitional care. Highlighting the need for further study of the implementation of shared care models to design strategies for care delivery during transitions to adult care.